ANALISIS KOMUNIKASI ORGANISASI DALAM MEMPERKUAT KESELAMATAN KERJA DI TERMINAL PETIKEMAS - Muhammad Audy Setiawan; Yovi Bathesta (LPSDI Bina Patria, 2024)
Occupational safety in Indonesia faces significant challenges in its efforts to protect the physical and mental health of workers, especially in the context of high-risk work environments such as ports. Although Occupational Safety and Health (OSH) aims to create safe and efficient working conditions, data on Work Accident Insurance (JKK) claims show an alarming upward trend, highlighting the urgency of implementing more effective OSH policies. This research explores how organizational communication plays a role in strengthening work safety at Koja Container Terminal, a location with a high risk of accidents due to loading and unloading activities. The main focus of the research was the effectiveness of vertical, horizontal and diagonal communication in disseminating safety information and managing OHS policies. The findings show that vertical communication, such as safety instructions from management and reporting from field staff, as well as horizontal communication between supervisors, is essential to ensure consistency in the implementation of safety policies. In addition, diagonal communication that enables quick reporting of incidents also contributes to better risk management. To improve the effectiveness of communication, regular training and facilitation of constructive feedback are recommended, in order to strengthen the safety culture, minimize accidents and increase productivity in the work environment.